Reconstruction of Fulfilling the Rights of Domestic Helpers in Employment Relations as a Form of Respect for Human Rights - Shohib Muslim; Shinta Hadiyantina; Hudriyah Mundzir; Khrisna Hadiwinata; Dina Imam Supaat (Yuridika, 2023)
The state guarantees welfare for its people, including domestic servants who are guaranteed constitutional rights. However, in statutory regulations, guarantees for legal protection do not apply to domestic workers who work in the informal sector, while domestic workers who work in the formal sector get guaranteed legal protection, as stated in Law No. 11 of 2020 regarding the employment creation cluster. Techniques implemented in research in the form of presentation of concepts, theories and arguments that are useful in studying and analyzing phenomena that occur based on applicable regulations are called normative juridical techniques. Regulations on employment relations norms that place more importance on economic liberalization are listed in Article 1 paragraph 15 and Article 50, where these articles are also the cause of the legal blurring of norms contained in Article 1 paragraph 3. A domestic worker needs a guarantee of legal protection because he has a weak position. The issue of vague norms (vague of norms) contained in Article 1 paragraph 3 is caused by inconsistencies between Article 1 paragraph 15 and Article 1 paragraph 3 and the article that strengthens it, namely article 50, which should implicitly apply to domestic workers.